2019
DOI: 10.3390/w11061183
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Efficiency of Red Mud for the Degradation of Olive Mill Wastewater through Heterogeneous Fenton’s Process

Abstract: Olive mill wastewater is a challenging effluent, especially due to its toxicity related to the presence of phenolic compounds. Fenton's process was analysed on the abatement of phenolic acids typically found in this kind of effluents. To overcome the main drawback of Fenton's process, a waste from the aluminium industry commonly called red mud was used as a heterogeneous source of iron. The adsorption of simulated effluent on the red mud was negligible. Therefore, the degradation of phenolic acids during Fento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…In this case, the amount of unused oxidant could put formed hydroxyl radicals to be in severe competitive environment with other organic contaminants influencing oxidation efficiency. 20,21) In other perception, those hydroxyl radicals available in the solution system might be consumed by the excess amount of H 2 O 2 . 22) Furthermore, the effect of TiO 2 and ZnO loading on COD removal rate from PRE was also displayed in .…”
Section: Effect Of Fenton and Catalyst Dosagementioning
confidence: 99%
“…In this case, the amount of unused oxidant could put formed hydroxyl radicals to be in severe competitive environment with other organic contaminants influencing oxidation efficiency. 20,21) In other perception, those hydroxyl radicals available in the solution system might be consumed by the excess amount of H 2 O 2 . 22) Furthermore, the effect of TiO 2 and ZnO loading on COD removal rate from PRE was also displayed in .…”
Section: Effect Of Fenton and Catalyst Dosagementioning
confidence: 99%
“…Domingues et al (2019) used red mud as a heterogeneous source of iron for Fenton process to degrade phenolic acids. Results showed that phenolic acids were degraded totally after 60 min under optimal conditions, and the remained hydrogen peroxide was the source of toxicity after treatment.…”
Section: Chemical Processesmentioning
confidence: 99%
“…The oxidation reactions generally follow as below Eq. (1)-(4) (Sani et al, 2020 (Buthiyappan and Raman, 2019;Domingues et al, 2019;Xia et al, 2017). In recent years, metal oxides, which have properties such as low toxicity, low cost and chemical stability as catalysts in the Heterogeneous Fenton process, have been of great interest.…”
Section: Introductionmentioning
confidence: 99%